Mental Health Stigma and its Impact on Help-Seeking Behavior - Omondi, Kelly (International Journal of Humanity and Social Sciences, 2024)
Purpose: The general objective of the study was to explore mental health stigma and its impact on help seeking behaviour. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to mental health stigma and its impact on help seeking behaviour. Preliminary empirical review revealed that mental health stigma, manifesting as public, self, and institutional stigma, significantly impeded help-seeking behavior. Public stigma led to social exclusion and reinforced negative self-perceptions, while self-stigma resulted in feelings of shame and low self-worth, deterring individuals from seeking treatment. Institutional stigma, characterized by discriminatory policies and inadequate resources, further hindered access to care. Effective strategies to combat stigma included public awareness campaigns, empowering interventions, and policy reforms, aiming to create a more supportive environment and improve mental health outcomes. Unique Contribution to Theory, Practice and Policy: The Social Identity Theory, Labeling Theory and Theory of Planned Behaviour may be used to anchor future studies on mental health stigma and its impact on help- seeking behaviour. The study recommended addressing mental health stigma through theoretical expansion, practical interventions, and policy changes. It emphasized the interconnected nature of public, self, and institutional stigma and suggested tailored anti-stigma interventions, such as contact-based approaches and training programs for practitioners. Policy recommendations included mental health parity laws, early mental health education, and public awareness campaigns. Practical suggestions focused on reducing public stigma through media and educational initiatives, addressing self-stigma with cognitive-behavioral therapy and peer support groups, and enhancing access to care with telehealth services and culturally competent practices.